Efficacy and putative mechanisms of action of nutraceuticals in the management of erectile dysfunction: a narrative review - Lorenzo Romano; Michele Musone; Luigi Napolitano; Lorenzo Spirito; Celeste Manfredi; Davide Arcaniolo; Ferdinando Fusco; Biagio Barone; Antonio Tufano; Pier Paolo Prontera; Ugo Amicuzi; Antonio Cioffi; et al. (Journal of Men's Health)
Erectile dysfunction (ED) is a common condition in the male population and isinfluenced by numerous pathophysiological factors. Recently, interest in nutraceuticals and natural remedies as complementary or alternative therapies to traditional pharmacological treatments has increased exponentially. This narrative review aims to analyze the impact of the most studied nutraceuticals in the treatment of ED, analyzing their mechanisms of action, clinical efficacy and safety. Much attention has been paid to compounds such as L-arginine, as well as several medicinal plants including ginseng, maca, Tribulus terrestris and antioxidant substances such as resveratrol and Pycnogenol. These natural products have different mechanisms of action, including modulation of endothelial function, reduction of oxidative stress and balance of sex hormones, thus addressing multiple therapeutical targets for the management of ED. However, despite promising results reported in various preclinical and clinical studies, several limitations to the use of nutraceuticals for ED persist, including variability in study designs, lack of standardized dosages of various compounds and lack of long-term safety evaluations. In fact, although nutraceuticals generally demonstrate a favorable safety profile compared to traditional drugs, they are not completely exempt from possible side effects. Furthermore, issues such as inconsistent patient adherence to treatment and potential interactions with drug therapies require further research and investigation. Therefore, high-quality, adequately sized clinical trials to better evaluate the efficacy and safety of these compounds, alone or in combination with conventional, widely adopted therapeutic regimens are warranted. In conclusion, nutraceuticals present a promising therapeutic option in the management of ED, potentially capable of improving clinical outcomes and patients’ quality of life when integrated into an all-inclusive therapeutic strategy.